Penerapan FMEA untuk Mengoptimalkan Kualitas Produk Jerrycan Plastik di Departemen Moulding PT. PHPO Belawan - Boangmanalu, Chandra Septian; Novarika AK, Wirda; Sibuea, Siti Rahmah (Fakultas Teknik Universitas Tulang Bawang, 2025)
The production of plastic jerrycans using the injection molding process still results in defective products during shipment to customers, leading to increased transportation and production costs. Data from December 2023 shows that the defect percentage for 20-liter yellow jerrycans reached 3%, while for 25-liter yellow jerrycans it was 5%, causing the production target to fall short. To address this issue, the Failure Mode and Effect Analysis (FMEA) method was used to identify potential failures, assess risks, and determine corrective actions for the most critical problems. The research revealed that the highest defect rate occurred in the topload test, with 36% for the 20-liter jerrycans and 39% for the 25-liter jerrycans, with an RPN value of 512. The primary cause of the topload defects was due to machine factors, specifically uneven jerrycan thickness caused by the drop of material in the diehead. To control this issue, the diehead was locked at the thinner section of the jerrycan body. Keywords: Diehead, Jerrycan, Molding, Quality, Topload